Phase angle and its relationship with biological markers of health. - Hernández Almanza, Samuel José
Phase angle behaves as a nutritional indicator, as a health indicator, and it is used to monitor the function of cell membranes. Objective: To determine the relationship between phase angle and different biological markers to determine health risks at early ages. Materials and methods: 57 healthy men were evaluated, a bioimpedance test was applied with the Inbody S10® equipment, leg power test with the horizontal jump test with feet together. The statistical analysis was performed with Jamovi 2.2.5 Solid® software. Results: Descriptive statistics of the biological, morphological, and functional components were reported, and Pearson’s correlation tests were applied between the same groups of variables against the phase angle as the dependent variable. Linear regression was determined for variables with moderate or high correlations and ANNOVA. Conclusions: Correlation was found between phase angle and muscle mass, against the other variables, the level of correlation was not very high or significant. The importance of muscle development in the population is confirmed by health parameters even at early ages. Discussion: Normality is found among the morphological components. However, the difference between fat percentage and muscle mass concerning the phase angle is evident.